REVITALISASI BANGUNAN EX-CHARTERED BANK DI KAWASAN KOTA TUA JAKARTA MELALUI PENYUNTIKAN INTERIORITAS - Ilma Badryah Hidayah Jamaludin; Suwardana Winata (Jurusan Arsitektur dan Perencanaan, 2022)
Starting with the many buildings that were built during the Dutch period, then underwent a change of function, renewal and abandoned so that it became a building that was not maintained or maintained. The Old Town area is an area known for its many historical relics in the form of buildings, art and much more. However, the many changes in function that have made the Old Town Area lose its original function. One of them is the heritage building of the Ex-Chartered Bank of India, Australia & China which is located on a road hook which had its initial function as a bank and then underwent changes which ended with the abandonment of the building. Through the Revitalization Project of Ex-Chartered Bank Heritage Buildings in the Old City Area as an Art Center, Gallery and Performance Place by injecting interiority as an effort to revive the building, it is hoped that it can restore relics, works and can become a place or container for art activities that are starting to be abandoned. So that it can restore the image of the area to be Old Batavia with the existing art. Keywords: acupuncture architecture; injection of interiority; interior architecture; revitalization; social and culture Abstrak Diawali dengan banyaknya bangunan yang dibangun pada masa Belanda, lalu mengalami pergantian fungsi, pembaharuan serta ditinggalkan sehingga menjadi bangunan yang tidak terjaga maupun terawat. Kawasan Kota Tua merupakan kawasan yang dikenal dengan banyaknya peninggalan sejarah berupa bangunan, seni dan masih banyak lagi. Namun banyaknya pergantian fungsi yang dialami menjadikan Kawasan Kota Tua kehilangan fungsi awalnya. Salah satunya bangunan peninggalan Ex-Chartered Bank of India, Australia & China yang berada dihook jalan yang memiliki fungsi awal sebagai bank lalu mengalami perubahan yang diakhiri dengan terbengkalainya bangunan. Melalui proyek Revitalisasi Bangunan Warisan Ex-Chartered Bank Di Kawasan Kota Tua Sebagai Pusat Seni, Galeri dan Tempat Pertunjukan dengan penyuntikan interioritas sebagai upaya menghidupkan bangunan diharapkan dapat mengembalikan peninggalan, karya dan dapat menjadi tempat atau wadah dalam aktivitas seni yang mulai ditinggalkan. Sehingga dapat mengembalikan citra kawasan menjadi Old Batavia dengan seni yang ada.